Peningkatan Akses Pendidikan Menengah Berorientasi Keadilan di Kabupaten Pati Jawa Tengah - Suroso, Suroso (IAIN Ponorogo, 2018)
Education is very important to develop human resources. The objective of this study is to analyze the defelopment policy for access equityÂ of secondary education. This research uses descriptive-quantitative approach. The data consist of primary and secondary ones. Data collecting is conducted by using observation and interview. The analysis of data uses descriptive one. There are 3 findings in the research. Firstly, the distribution of secondary education development in the study area is less equally. Secondly, the district which becomes a priority of secondary education development is the district which has the smallest ratio between proportion of existing secondary education toward proportion of population. Thirdly, the most potential site for the secondary education development oriented to optimazation accessibility is the site in the centre by incorporating geographical factor and population. However, selecting a land of the site for secondary education development should meet the normative standards in the regulation.Ø¥Ù Ø§ÙØªØ±Ø¨ÙØ© Ù ÙÙ Ø© ÙØªØ·ÙÙØ± Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ©. ØØ§ÙÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« ØªØÙÙÙ ÙØ±Ø§Ø± ØªØ¹Ù ÙÙ Ø§ÙØØµÙÙ Ø¹ÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙÙ Ø§ÙÙ Ø±ØÙØ© Ø§ÙÙ ØªÙØ³Ø·Ø©. ÙØ§Ø³ØªØ®Ø¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙÙ Ø¯Ø®Ù Ø§ÙÙØµÙÙ Ø§ÙÙÙÙÙ. ÙØªØ´ØªÙ Ù Ø¨ÙØ§ÙØ§Øª Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø§ÙØ£Ø³Ø§Ø³ÙØ© ÙØ§ÙØ¨ÙØ§ÙØ§Øª Ø§ÙØ«Ø§ÙÙÙØ©. ÙÙØ°Ù Ø§ÙØ¨ÙØ§ÙØ§Øª ØªÙØ¬Ù Ø¹ Ø¹Ù Ø·Ø±ÙÙ Ø§ÙÙ ÙØ§ØØ¸Ø© ÙØ§ÙÙ ÙØ§Ø¨ÙØ©. Ø£Ù Ø§ Ø·Ø±ÙÙØ© ØªØÙÙÙÙØ§ ÙØ¨Ø§ÙØªØÙÙÙ Ø§ÙÙØµÙÙ. ØØµÙ Ø§ÙØ¨Ø§ØØ« Ø¹ÙÙ ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ«Ø Ø£ÙÙØ§ : Ø¥Ù ØªØ¹Ù ÙÙ Ø§ÙØ¨ÙØ§Ø¡ Ø§ÙØªØ±Ø¨ÙÙ ÙÙÙ Ø±ØÙØ© Ø§ÙÙ ØªÙØ³Ø·Ø© ÙÙ Ù ÙØ¶Ø¹ Ø§ÙØ¨ØØ« ÙÙ ÙÙÙ Ø´Ø§Ù ÙØ§ ÙÙØ¬Ù ÙØ¹Ø Ø«Ø§ÙÙØ§ : Ø¥Ù Ø§ÙÙ ÙØ·ÙØ© ÙØ§ÙÙØ¯Ù ÙÙØ¨ÙØ§Ø¡ Ø§ÙØªØ±Ø¨ÙÙ ÙÙÙ Ø±ØÙØ© Ø§ÙÙ ØªÙØ³Ø·Ø© ÙÙØ§ Ø§ØªØ¬Ø§Ù ÙÙØ¹Ø¯Ø§ÙØ©Ø ÙÙ Ø§ÙÙ ÙØ·ÙØ© Ø§ÙØªÙ ÙÙØ§ ÙØ³Ø¨Ø© Ø£ØµØºØ± Ø¨ÙÙ ÙØ³Ø¨Ø© ÙØ¬ÙØ¯ Ø§ÙØªØ±Ø¨ÙØ© ÙÙÙ Ø±ØÙØ© Ø§ÙÙ ØªÙØ³Ø·Ø© ØªØ¬Ø§Ù ÙØ³Ø¨Ø© Ø§ÙÙ ÙØ§Ø·ÙÙÙØ ÙØ«Ø§ÙØ«Ø§ : Ø§ÙÙ ÙØ·ÙØ© Ø§ÙÙ Ù ÙÙØ© ÙÙØ¨ÙØ§Ø¡ Ø§ÙØªØ±Ø¨ÙÙ ÙÙÙ Ø±ØÙØ© Ø§ÙÙ ØªÙØ³Ø·Ø© Ø§ÙÙ ØªØ¬Ù Ø¥ÙÙ Ø§ÙØªØ¹Ù ÙÙ Ø§ÙØªØ±Ø¨ÙÙ ÙÙ Ø§ÙÙ ÙØ·ÙØ© Ø§ÙÙØ³Ø·Ù Ø¨Ø§Ø¹ØªØ¨Ø§Ø± Ø§ÙÙ ÙÙØ¹ Ø§ÙØ¬ØºØ±Ø§ÙÙ ÙØ§ÙÙ ÙØ§Ø·ÙÙÙ. ÙÙÙÙ Ø§Ø®ØªÙØ§Ø± Ø§ÙÙ ÙØ§Ù ÙÙØ¨ÙØ§Ø¡ Ø§ÙØªØ±Ø¨ÙÙ ÙÙÙ Ø±ØÙØ© Ø§ÙÙ ØªÙØ³Ø·Ø© ÙØ°Ø§ ÙØ§Ø¨Ø¯ Ù Ù Ø§Ø³ØªÙÙØ§Ø¡ Ø§ÙÙ Ø¹Ø§ÙÙØ± Ø§ÙÙØ¸Ø§Ù ÙØ©.